Commercial critical systems and critical infrastructure protection : a future research agenda - Leitch, Shona (2007)
Secure management of Australia’s commercial critical infrastructure presents ongoing challenges to owners and the government. Although it is currently managed through high-level information sharing via collaboration, but does this suit the commercial sector. One of the issues facing Australia is that the majority of critical infrastructure resides under the control of the business sector and certain aspects such of the critical infrastructure such as Supply Chain Management (SCM) systems are distributed entities and not a single entity. The paper focuses upon the security issues associated with SCM systems and critical infrastructure protection.<br /